Tingkat Keuntungan Petani Kubis (Brassica oleracea Var. Capitata) di Kabupaten Agam - Fauzi, Dian; Syahrial, Syahrial (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
The physical condition of the region. However, in carrying out farming, farmers face several obstacles. These factors can also affect the income and profits received by farmers. Therefore, the costs and revenues in aspects so that the income received by farmers can meet their daily needs. The dynamic effect of cabbage prices significantly affects the income received by farmers. However, this does not discourage farmers from farming cabbage, even though the risk is in the rainy season because it can manifest a relatively high level-profit level with the correct calculation. This study aims to analyze the profile level received by cabbage farmers in Agam Regency. The research was conducted in Baso Sub-district. The research method used is farming analysis. The study found that cabbage farmers’ profit in the Agam District was Rp. 435.25/kg with a profit rate of 4,48 % and an R/C ratio of 1.19.